The shape and speciation of Ag nanoparticles drive their impacts on organisms in a lotic ecosystem. Issue 10 (16th September 2020) - Auffan, M.; Santaella, C.; Brousset, L.; Tella, M.; Morel, E.; Ortet, P.; Barakat, M.; Chaneac, C.; Issartel, J.; Angeletti, B.; Levard, C.; Hazemann, J.-L.; et al.
Abstract : Silver nanomaterials with different shapes (spheres, plates, wires, rods, cubes) are valued by industries and scientists for their shape-dependent properties which make them useful for diverse applications. Abstract : Silver nanomaterials with different shapes (spheres, plates, wires, rods, cubes) are valued by industries and scientists for their shape-dependent properties which make them useful for diverse applications. In a safer-by-design perspective, controlling the shape of Ag nanomaterials could be an option to increase their properties while lowering either their hazard or their exposure potentials. Nine indoor aquatic mesocosms reproducing a lotic ecosystem were contaminated with chronic low-level additions of Ag nanospheres (Sp-Ag) and nanoplates (Pl-Ag) for a month. A shape-dependent impact under such environmentally relevant exposure conditions was observed. Pl-Ag induced a moderate oxidative stress in adult Gammarus fossarum (after molting) and a hormesis effect on planktonic microbial communities, while Sp-Ag had no effect. In an environmental risk perspective, our results highlight which ecological niches of a lotic ecosystem would be more impacted by Pl-Ag: (i) >72% of the total Ag was found fully sulfidized in surficial sediment and had only a moderate impact on benthic macro-organisms, (ii) only 11% to 15% of the Ag remained in the water column after 1 month, but Ag was under a more reactive speciation that impacts the planktonic community.